Advancing the Conceptualization of Willingness to Communicate in China’s English Education Landscape: Insights from English Corners - Li, Michael; Huang , Huan; Yu , Daimeng (Polyglot: Journal of Linguistics, Literature, and Language Education, 2026)
English corners, as informal student-led English-speaking spaces, are widely established across Chinese universities as a response to exam-oriented English instruction, offering opportunities for real communication beyond test preparation. Yet empirical research on learners’ willingness to communicate (WTC) in these contexts remains limited. Guided by Self-determination Theory, this qualitative study examines how peer-led English corners shape students’ WTC. Data from 36 undergraduate students were collected through focused essays, asynchronous peer response letters, and semi-structured interviews. Thematic analysis revealed that learners’ WTC was more intrinsically motivated in English corners than in classroom settings, supported by greater autonomy (e.g., topic choice), competence (e.g., rehearsal), and relatedness (e.g., peer encouragement). Learners also pursued intrinsic goals such as enjoyment, self-growth, and connection. The study positions English corners as motivational ecologies that foster sustainable second language engagement and highlights asynchronous peer response as a novel, low-pressure tool for emotional support and reflective strategy sharing. Implications suggest informal peer-led spaces complement formal instruction by enhancing self-determined motivation, contributing theoretically and methodologically to socially oriented language education.